(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study explored the relationship between three independent variables (interest, motivation, andsense of self) and career aspiration of Vocational and Technical Education Students. Threehypotheses were formulated to guide the study. Correlational survey design was adopted for the study. Students from all the eight technical colleges in Ogun State constituted the population for the study. Atotal of 100 technical college students, selected through simple random sampling, eventuallyparticipated in the study. Sense of self scale, Jackson Vocational interest inventory, Motivationfor occupational preference scale, and Career Aspiration Scale - Revised were used for datacollection. Cronbach Alpha was used to estimate the reliability of the instruments, the four instruments yielded reliability coefficients of 0.73, 0.81, 0.83 and 0.79 respectively. Thequestionnaires were collected immediately after administration. Mean, standard deviation, andPearson Product Moment Correlation (PPMC) was used to analyse the data. The study showedthat there is a significant relationship between sense of self and career aspiration of vocational andtechnical education students. There is a significant relationship between motivation and career aspiration of Vocational and technical education students. Furthermore, there is a significant relationship between interest and career aspiration of Vocational and technical education students. Based on these findings, it was recommended that measures should be taken to improve sense of self of students in vocational and technical colleges to enable them understand their strengths, weaknesses, values, and beliefs. Also, efforts should be made towards increasing students’ motivation to excel intheir vocational and technical education program and set high career aspirations. Furthermore, vocational counselling and guidance services should be provided and strengthened in all schools toascertain students’ vocational interest and also improve their sense of self.